LEARNING MODEL METHODS EMOTIONAL DEMONSTRATION (EMO DEMO) IN PREVENTION OF NON-COMMUNICABLE DISEASES: QUASI-EXPERIMENTAL STUDY - Winda Triana; Pahrur Razi; Ervon Veriza; Solihin Sayuti (OPI Napoli, 2022)
Background. The development of science and technology in the field of medicine encourages experts to always conduct research on various diseases, including one of them is the incidence of infectious diseases in order to overcome suffering and death due to these diseases.This study aimed to analyze the effectiveness of the emo demo method in increasing knowledge and skills about the prevention of non-communicable diseases. Methods. This quasi-experimental study using two groups of pretest-posttest design involved 100 participants, whose data were collected using a questionnaire and tested using the Wilcoxon test. Results. Both knowledge and skills variables show differences before and after the intervention of providing education, namely there is an increase in knowledge and skills to prevent non-communicable diseases. There are different mean values ​​between pre-test and post-test knowledge and skills, meaning that mathematically indicates there are differences in knowledge and skills before and after Emo Demo. Conclusion. The Demonstration Emotional Method learning model is effective in increasing students' knowledge and skills about preventing non-communicable diseases.